Solve the following equation 6r + 2 = 3 + 3r + 1
Solution
Given the equation 6r + 2 = 3 + 3r + 1
The like terms in the equation 6r and 3r as well as 2, 3 and 1
Thus, we say bring like terms together as follows
6r + 2 = 3 + 3r + 1 (original equation)
6r – 3r = 3 + 1 – 2 (bringing
like terms together)
You noticed in the above that +3r in the right hand side (RHS) crosses to the left hand
side (LHS) to become -3r
Also, +2 in the left hand side (LHS) crosses the equality sign to the right hand
side (RHS) to become -2
6r – 3r = 3 + 1 – 2
3r = 2
The coefficient of r is 3. To get r, we now
divide both sides by 3 (coefficient of r) as follows
3r/3 = 2/3
r = 2/3
Check for correctness
The given equation is 6r + 2 = 3 + 3r + 1
LHS = 6r + 2
= 6*2/3) + 2
= 4 + 2
= 6
RHS = 3 + 3r + 1
= 3 + 3*2/3 + 1
= 3 + 2 + 1
= 6 (Same
as LHS)
Comments
Post a Comment